Breast Cancer Resistance Protein: A Potential Therapeutic Target for Cancer - Mehendale-Munj, Sonali; Sawant, Shivangi (Current Drug Targets, 2021)
Breast Cancer Resistance Protein (BCRP) is an efflux transporter responsible for causing multidrug resistance (MDR). It is known to expel many potent antineoplastic drugs, owing to its efflux function. Efflux of chemotherapeutics because of BCRP develops resistance to many drugs, leading to failure in cancer treatment. BCRP plays an important role in physiology by protecting the organism from xenobiotics and other toxins. It is a half-transporter affiliated to the ATP- binding cassette (ABC) superfamily of transporters, encoded by the gene ABCG2 and functions in response to adenosine triphosphate (ATP). Regulation of BCRP expression is critically controlled at molecular levels, which help in maintaining the balance of xenobiotics and nutrients inside the body. Expression of BCRP can be found in brain, liver, lung cancers and acute myeloid leukemia (AML). Moreover, it is also expressed at high levels in stem cells and many cell lines. This frequent expression of BCRP has an impact on the treatment procedures and, if not scrutinized, may lead to the failure of many cancer therapies.
Keywords: mitoxantrone-resistance protein